2018
DOI: 10.21315/ijaps2018.14.2.3
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Education on Income Inequality in Selected Islamic Countries

Abstract: The impact of education on income inequality remains a challenging issue at the core of economic debates. The present study attempts to investigate the effect of income inequality in a selection of Islamic countries during 1990-2013. Method of panel data has been implemented, and the fixed effects are examined against the random ones by the Hausman test. The impacts of gross domestic product (GDP) and training at primary, secondary and university levels on income inequality is investigated in the selected Isla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
22
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 35 publications
5
22
1
3
Order By: Relevance
“…With the number of students in the province, different from the Chiswick study (1971) who pointed out that increasing the proportion of students participating in higher education would help raise incomes for women, this research found that the number of student per 1000 population exerts a negative effect on women's incomes. This result is similar to that of Shahabadi et al (2018) who argue that increasing the number of students participating in higher education will increase the gender pay gap due to the high cost of such education and the lack of economic support from the government. In more men-favored society the rate of women participating in higher education is not high.…”
Section: Research Resultssupporting
confidence: 86%
“…With the number of students in the province, different from the Chiswick study (1971) who pointed out that increasing the proportion of students participating in higher education would help raise incomes for women, this research found that the number of student per 1000 population exerts a negative effect on women's incomes. This result is similar to that of Shahabadi et al (2018) who argue that increasing the number of students participating in higher education will increase the gender pay gap due to the high cost of such education and the lack of economic support from the government. In more men-favored society the rate of women participating in higher education is not high.…”
Section: Research Resultssupporting
confidence: 86%
“…Meanwhile, supporting this finding, Chongvilaivan dan Kim (2016) finds that education gaps in Indonesia dominantly lead to income inequality increases. A positive higher education-income inequality relationship is also found in emerging developing countries (Coady & Dizioli, 2018) and Islamic countries (Shahabadi et al, 2018) like Indonesia. In addition, Wells (2006) mentions numerous studies that support the positive relationship between education and income inequality, including Barro (2000).…”
mentioning
confidence: 84%
“…The positive relationship between education infrastructure and income inequality could be explained by unequal access, in particular to higher education, between the two income groups due to financial constraints of the poor (Chongvilaivan & Kim, 2016;Muttaqin, 2018;Wicaksono et al, 2017) and high educational cost (Shahabadi et al, 2018). Using data in 2007 and a Theil decomposition analysis, Chongvilaivan and Kim (2016) claim that education gaps in Indonesia dominantly lead to income inequality increases.…”
Section: Wiastuti Nurdinamentioning
confidence: 99%
See 1 more Smart Citation
“…The link between education and income inequality has long been a source of economic debate. According to Shahabadi et al (2018), wealth disparity harmed the Islamic world between 1990 and 2013. Their research found that primary and secondary school enrollment has a statistically significant negative influence on income inequality, but university enrollment has a statistically significant positive effect.…”
Section: Synthesismentioning
confidence: 99%